2022
DOI: 10.1021/acsnano.2c00893
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane-Camouflaged Nanocarriers with Biomimetic Deformability of Erythrocytes for Ultralong Circulation and Enhanced Cancer Therapy

Abstract: Despite considerable advancements in cell membrane-camouflaged nanocarriers to leverage natural cell functions, artificial nanocarriers that can accurately mimic both the biological and physical properties of cells are urgently needed. Herein, inspired by the important effect of the stiffness and deformability of natural red blood cells (RBCs) on their life span and flowing through narrow vessels, we report the construction of RBC membrane-camouflaged nanocarriers that can mimic RBCs at different life stages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 42 publications
1
68
0
Order By: Relevance
“…Yunqiu Miao et al developed a novel NPs system whose surface was decorated with natural RBC membranes [ 50 ]. This RBC-mimic system was constructed based on RBC membranes and poly (ethylene glycol) diacrylate (PEGDA) hydrogel nanoparticles, and due to the RBC membrane, this system exhibited many gorgeous properties, including evading the immune system efficiently, penetrating narrow tissue extracellular space of tumors and accumulating in diseased tissues ( Figure 4 A).…”
Section: Biomimetic Approach To Harness Protein Coronamentioning
confidence: 99%
See 2 more Smart Citations
“…Yunqiu Miao et al developed a novel NPs system whose surface was decorated with natural RBC membranes [ 50 ]. This RBC-mimic system was constructed based on RBC membranes and poly (ethylene glycol) diacrylate (PEGDA) hydrogel nanoparticles, and due to the RBC membrane, this system exhibited many gorgeous properties, including evading the immune system efficiently, penetrating narrow tissue extracellular space of tumors and accumulating in diseased tissues ( Figure 4 A).…”
Section: Biomimetic Approach To Harness Protein Coronamentioning
confidence: 99%
“…( A ) The RBC-mimic system (RBC-ENPs) was constructed based on the RBC membrane and poly (ethylene glycol) diacrylate (PEGDA) NPs. The RBC cell membrane decoration endowed this system with the ability of immune escape by controlling the composition of the protein corona and deformation for better tumor penetration [ 50 ]. Copyright 2022, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The biconcave morphology of erythrocytes gives them excellent deformability and allows for smooth passage through capillaries of several microns. Importantly, erythrocytes are considered an effective bionic drug carrier due to their long circulation time and easy availability in the body ( 114 ).…”
Section: Cell Membrane-modified Nanomaterialsmentioning
confidence: 99%
“…In vivo results showed that doxorubicin-loaded RBC-ENPs exhibited superior antitumor efficacy to the first-line chemotherapeutic drug PEGylated doxorubicin liposomes. 102 These biomembrane-camouflaged nanocarriers exhibit superior efficacy and high safety for disease treatment, which stands for a promising direction of nanocarriers.…”
Section: Biomembrane-camouflaged Nanocarriersmentioning
confidence: 99%